How to improve the science process skills of biology education students on photosynthesis topic? - A Yuniarti; B Supriatno; E Nureni (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The DP4 learning strategy in this research is the acronym of Demonstration method, Practical work-discussion1 method, Presentation-discussion1 method, Practical work-discussion2 method, and Presentation-discussion2 method. This study aims to describe the effect of applying DP4 learning strategy to Science Process Skills (SPS) of biology education students on photosynthesis topic. The research method is a weak experiment, with the research design “The One-Group Pretest-Posttest Design”. The implementation of the study involved 36 biology education students at one of the universities in Pontianak. The research instrument used is in the form of test equipment, assessment rubric, and questionnaire. Data were analyzed using Microsoft Excel and SPSS 24 Program. The statistical results show that DP4 leraning strategy has an effect on improving biology education students science process skills on photosynthesis topic. This due to the topic of photosynthesis that is learned through demonstration, practical work-discussion, and presentation-discussion activities to direct the students to observe the facts that appear in experiment, to formulate hypotheses, to determine the independent variables, bound variables and control variables in the experiment, to experiment, create data tables and write experiment data, interpreting and analyzing experimental data, connecting experimental variables, and make a conclusions from experimental results. This DP4 learning strategy can be utilized by educators in learning photosynthesis topic.